Disconnected Pancreatic Duct Syndrome. Issue 1 (January 2015) - Nadkarni, Nikhil A.; Kotwal, Vikram; Sarr, Michael G.; Swaroop Vege, Santhi
<x xml:space="preserve">Abstract</x> Abstract Disconnected pancreatic duct syndrome is a sequela of necrotizing pancreatitis or pancreatic trauma in which necrosis of a segment of the pancreas leads to lack of continuity between viable secreting pancreatic tissue (eg, body or tail) and the gastrointestinal tract. The endoscopic retrograde cholangiopancreatography showing total cutoff of the pancreatic duct along with an enhancing distal pancreas on contrast-enhanced computed tomography remains the criterion standard for diagnosis. Recently, the evolving literature supports a role for magnetic resonance cholangiopancreaticography, especially with secretin stimulation. A multidisciplinary approach is extremely important in the management of this condition. Conservative measures are usually not helpful, and interventional radiology, endoscopic, or surgical intervention is almost always needed for management of these patients. Recently, endoscopic ultrasonography–guided drainage procedures in conjunction with endoscopic retrograde cholangiopancreatography–assisted pancreatic duct stenting have emerged as a novel technique to manage this condition. The aim of this review was to give a detailed overview about the diagnosis and management of disconnected pancreatic duct syndrome with emphasis on the changing paradigm in endoscopic and surgical management.